Analysis of The Effect of Entrepreneurship Education and Motivation on Increasing Female Entrepreneurial Intention Mediated by Self-Efficacy at Binus Alam Sutera - Ardhia Devitha Nareswari; Chiesa Krisnaya Vendra; Abdul Rohman (Riviera Publishing, 2025)
This study aims to analyze the relationship between entrepreneurship education, entrepreneurial motivation, and entrepreneurial intention among university students in Indonesia, with a particular focus on the mediating role of self-efficacy. Entrepreneurship is widely recognized as a key driver of national economic growth and social transformation; however, Indonesia continues to experience a relatively low level of entrepreneurial activity, particularly among women and youth. This study employs a quantitative approach to examine the relationships between entrepreneurship education and motivation. Data were collected through a structured online survey using a questionnaire. The analysis focuses on hypothesis testing by measuring specific variables through statistical methods. The results indicate that entrepreneurship education has a significant positive effect on entrepreneurial motivation and self-efficacy, both of which contribute to stronger entrepreneurial intentions. Self-efficacy was found to partially mediate the relationship between entrepreneurship education and entrepreneurial intention, confirming that confidence in one’s entrepreneurial abilities serves as a crucial psychological bridge between learning and action. These findings highlight the importance of integrating experiential learning, mentorship, and digital entrepreneurship modules into university curricula to strengthen entrepreneurial self-efficacy and motivation. The study contributes to the growing body of literature on entrepreneurship education in developing countries and provides actionable insights for policymakers, educators, and universities in designing programs that cultivate entrepreneurial mindsets and promote inclusive economic empowerment.